Thinking through utilitarianism : a guide to contemporary arguments - Forcehimes, Andrew T. (Hackett Publishing Company, Inc., 2022)
Thinking Through Utilitarianism: A Guide to Contemporary Arguments offers something new among texts elucidating the ethical theory known as Utilitarianism. Intended primarily for students ready to dig deeper into moral philosophy, it examines, in a dialectical and reader-friendly manner, a set of normative principles and a set of evaluative principles leading to what is perhaps the most defensible version of Utilitarianism. With the aim of laying its weaknesses bare, each principle is serially introduced, challenged, and then defended. The result is a battery of stress tests that shows with great clarity not only what is attractive about the theory, but also where its problems lie. It will fascinate any student ready for a serious investigation into what we ought to do and what is of value.